Factor analysis for building trust in secondary school administrators: Confirmatory factor analysis - Kusuman, Piyanat; Sirisooksilp, Saowanee; Tuksino, Prakittiya (Edelweiss Applied Science and Technology, 2026)
This study intends to investigate the components and indicators of trust of secondary school administrators and the fit of the model of components and indicators of trust in the Northeastern area, Thailand. The design for this research is mixed-methods research under a multi-phase design. Phase 1 aims to determine the elements and dimensions of trust in principals. This is done by a review of literature and study of literature related to trust in trustees, which is then expert-rated. Qualitative data were analyzed using content analysis. Phase 2 confirms the goodness-of-fit of trust components and indicators among secondary school administrators in the northeast of Thailand. The sample includes four hundred principals and secondary school teachers from the Northeast region. The data were analyzed to examine model fit using CFA. Study of the components of trust in secondary school administrators and their indicators revealed five main components: Competence, Benevolence, Integrity, Reliability, and Openness. The goodness-of-fit indices of the model analyzed in secondary school administrators' trust factor consist of: 1) model of the components of trust among secondary school administrators in Thailand's Northeastern region: χ² = 72.887, df = 57, χ²/df = 1.279, p-value = 0.0764, comparative fit index (CFI) = 0.998, Tucker-Lewis index (TLI) = 0.997, root mean square error of approximation (RMSEA) = 0.026, and standardized root mean square residual (SRMR) = 0.008.